CFD simulations of single-phase flow in pulsed disc and doughnut columns: Axial dispersion and pressure drop. Issue 18 (12th December 2017) - Sarkar, Sourav; Singh, K. K.; Shenoy, K. T.
ABSTRACT: CFD simulations of pulsed disc and doughnut columns are performed to understand the effects of operating and geometric parameters on axial dispersion and pressure drop in single-phase flow. CFD simulations have been carried out using a two-step approach. In the first step, the flow field is obtained by solving the continuity and the momentum equations along with the equations of the standard k – ε model of turbulence. In the second step, the species transport equation is additionally solved to obtain the residence time distribution and hence the Peclet number and axial dispersion coefficient. The computational approach is validated by comparing its predictions with the experimental data reported in the literature and then used for detailed parametric analysis.